Chylothorax and necrotizing pneumonia as complications of vomiting and cough induced by placement of a gastric tube for enteral nutrition in a 8-year old boy with Crohn's disease - Wronowski, Michał; Kotowska, Maria; Krenke, Katarzyna; Albrecht, Piotr (Pediatria Polska - Polish Journal of Paediatrics, 2017)
A boy aged 8, with chronic diarrhoea, was admitted to clinic for diagnosis of Crohn's disease. The diagnosis was confirmed and total enteral nutrition initiated. Due to intolerance of oral intake, it was decided to insert gastric tube for nutrition. Two attempts of insertion were unsuccessful due to stubborn vomiting and cough – only minor amount of polymeric diet was administered. During next 24 hours the general state of patient worsened sharply. Dyspnoea and tachypnoea were observed, dull percussion sound and decreased breath sound were heard. The imaging of chest revealed presence of a fluid in the right pleural cavity. Pleural drain was inserted and yellow-white fluid (biochemical features of chylous and complicated parapneumonic effusion) was obtained. Chylothorax and necrotizing pneumonia were diagnosed. Pleural drainage was kept for next 12 days, along with antibiotics, fat free diet, albumins and intensive symptomatic treatment. The improvement of patient's general state and resolution of pulmonary changes were achieved. A rupture of thoracic duct leading to chylothorax in children due to stubborn vomiting has been already discussed in literature – however, such a case has never been described in association with Crohn's disease.